191 How do you get work experience during a national lockdown?. (17th August 2022) - Reeves, Tara; Davidson, Neil; Ball, Joanne; Courtney, Jack; Ella, Mx; ,
Abstract : Aims: The global pandemic stripped away time critical career experiences for a lot of young people. We aimed to minimise the losses to future careers and create a convenient platform that explores NHS job options for young people (YP). The aim was for this to be a project created and realised entirely by YP. Methods: YPAGne's initial idea was to create a podcast. Brainstorming quickly established YPs desire for audio as well as visual content. They wanted to pick their own speakers and create this themselves, rather than listen to a lecture. Thus, a live broadcast with an interactive element emerged. Starting with a logo competition (fig. 1) and then a pilot interview to establish technical issues, our YPAGne group produced interviews of NHS workers for monthly episodes of 'Nattering with the NHS'. Each episode, a YP volunteers as 'MC' to keep to time and introduce our podcast topic. Questions are pre-planned by YP but on the day, conversation allows off script moments. YPAGne members allocate roles so that social media platforms inc. instagram, twitter and facebook have live updates during the podcast (fig. 2). Hashtags were created and thus a space for followers to contribute to a Q&A after the interview, with questions fielded by YPAGne members in real time. Technology includes zoom for recording and a youtube channel for posting the finished episode (fig.3 and 4). A WhatsApp technical issues chat runs alongside the podcast for YP to problem solve on the spot. YPAG facilitators created a novel social media policy for information governance reasons which encompassed all platforms utilised. Advertising was via YP disseminating links through their schools social media platforms. Results: So far, YPAGne have chosen to interview: A research nurse A paediatric consultant An intercalating medical student 2 clinical psychologists (renal and cleft lip teams) Coming up! a junior doctor and a physio Feedback from YPAGne was excellent (fig.5) 'I am the twitter manager …it was an amazing feeling knowing that I could help engage the viewers and help to answer any of the burning questions that they may have thought of. In addition, I found it very informative for myself as I was able to slip some of my own questions in during the podcasts I was present for.' Conclusion: An incredible feat has been achieved by our YP with very minimal input from facilitators. Technology has assisted in this becoming successful and feedback was unanimously positive. The process of managing this was work experience in itself and the finished products not only a lasting testimony to YPAGne's skill but has produced re-watchable content to benefit future generations. We are hoping to expand our project nationally to initially mentor and then collaborate with other YPAG's; current discussions are ongoing with GOSH. We will be live, together, very soon. Watch this space!